Molecular Basis of Gastric Carcinoma -A Challenge for the Future Days - Rahman, Md Mizanur (Journal of Surgical Sciences, 2019)
Abstract not available Journal of Surgical Sciences (2012) Vol. 16 (2) : 52-53